2019
DOI: 10.1101/526897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MaXLinker: proteome-wide cross-link identifications with high specificity and sensitivity

Abstract: Protein-protein interactions play a vital role in nearly all cellular functions. Hence, understanding their interaction patterns and three-dimensional structural conformations can provide crucial insights about various biological processes and underlying molecular mechanisms for many disease phenotypes. Cross-linking mass spectrometry has the unique capability to detect proteinprotein interactions at a large scale along with spatial constraints between interaction partners.However, the current cross-link searc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…These interactions were further enriched by obtaining annotations on cross-linking peptides matched across pairs of interactions, disease related mutations and protein phosphorylation sites in the selected proteins. Crosslink data was collected from (Yugandhar et al, 2020;Schweppe et al, 2016;Klykov et al, 2020;Steigenberger et al, 2019;Klykov et al, 2018;Fasci et al, 2018;Eliseev et al, 2018;Gestaut et al, 2019;Klatt et al, 2020;Sabath et al, 2020;Mohamed et al, 2021), filtered for peptides assigned to only one sequence. Clinical missense variants associated with disease were collected from ClinVar.…”
Section: Protein Interaction Data and Annotationsmentioning
confidence: 99%
“…These interactions were further enriched by obtaining annotations on cross-linking peptides matched across pairs of interactions, disease related mutations and protein phosphorylation sites in the selected proteins. Crosslink data was collected from (Yugandhar et al, 2020;Schweppe et al, 2016;Klykov et al, 2020;Steigenberger et al, 2019;Klykov et al, 2018;Fasci et al, 2018;Eliseev et al, 2018;Gestaut et al, 2019;Klatt et al, 2020;Sabath et al, 2020;Mohamed et al, 2021), filtered for peptides assigned to only one sequence. Clinical missense variants associated with disease were collected from ClinVar.…”
Section: Protein Interaction Data and Annotationsmentioning
confidence: 99%
“…For MS3, ions were fragmented in the linear ion trap using higher-energy collisional dissociation (HCD) at 35% HCD energy. The cross-link search was performed using MaXLinker software (Yugandhar et al, 2020). The structure mapping of cross-links was performed using Xlink Analyzer (Kosinski et al, 2015) implemented in UCSF Chimera (Pettersen et al, 2004).…”
Section: Cross-linking Mass Spectrometry (Xl-ms)mentioning
confidence: 99%
“…Similarly, the large‐scale and proteome‐wide XL‐MS studies tend to identify much higher fraction of cross‐links from highly abundant complexes such as ribosome and proteasome compared to that of proteins with relatively lower abundance [20]. To examine this comprehensively, we compiled a set of 31,745 cross‐links among 4035 proteins from published datasets [21–38] and analyzed them in relation to the cellular abundance of the cross‐linked proteins, obtained from PaxDB [39] (3688 out 4035 proteins had abundance values in the PaxDB which contribute to 28,244 cross‐links in the dataset) (Figure 2A, 2B). The results showed that about 76% of the cross‐links map to the proteins that belong to the top 10% category in terms of their cellular abundance (Figure 2B).…”
Section: Coverage Of Xl‐ms Datasetsmentioning
confidence: 99%